Archispeak : an illustrated guide to architectural terms - Porter, Tom (Taylor & Francis, 2004)
Widely used in architectural circles in the heat of discussion, the recurrent use of particular words and terms has evolved into a language of design jargon. Commonly found in architectural literature and journalism, in critical design debate and especially in student project reviews, Archispeak can seem insular and perplexing to others and -- particularly to the new architectural student -- often incomprehensible. There is a need to translate architectural design concepts into spoken and written commentary -- each word in use embodying a precise and universally accepted architectural meaning. If we explore the vocabulary of this language we gain insight into good design practice and into collective understanding of what constitutes a refined architecture. This unique illustrated guide will help students understand the nuances of this specialized language and help them in communicating their own design ideas.